Рівень конкуренції на ринку борошна в країнах Європейського Союзу - Легеза, Дар’я Георгіївна; Сокіл, Яна Сергіївна; Куліш, Тетяна Володимирівна; Legeza, Darya; Sokil, Yana; Kulish, Tetyana (Запоріжжя : 2023, 2023)
UA: Стаття розкриває основні критерії вибору стратегічних країн для експорту борошна українськими виробниками. Основними показниками оцінки конкурентних позицій країн є торговий баланс, динаміка росту вартості імпорту, ціна імпорту, наявність підприємств, що виробляють хлібопекарську продукцію. В дослідженні встановлено, що основними країнами імпортерами борошна в Європейському Союзі є Франція, Німеччина, Румунія, Нідерланди, Ірландія, Польща. Високий потенціал для імпорту українського борошна має Велика Британія. Розраховано, що ринок імпорту борошна у 2021 році в ЄС становив 22% світового імпорту товару. Зазначено, вартість імпорту борошна поступово збільшується за останні 5 років. Україна сьогодні має незначний досвід реалізації борошна у країни ЄС. Вартість експорту в ЄС становить лише 0,11% від світового імпорту в ЄС, а середня вартість борошна – 401 $/тону. Відповідно до проведеного аналізу встановлено, що основні підприємства розташовані в Італії, Німеччині, Польщі. Обґрунтовано, що українським підприємствам слід звернути увагу на експорт продукції в Польщу, Нідерланди та Велику Британію як країни з найбільш привабливим конкурентним потенціалом. EN: The country's development model, as a result of military actions, has undergone changes, including in its foreign economic activities. Destruction of logistic chains, blockade of sea ports, expected reduction in sown areas for grain crops, and projected decrease in yield, leading to an increase in flour prices, may result in a decrease in the export volumes of Ukrainian flour and a loss of leading positions in the global agri-food market. However, abolition of customs duty by Europe will allow Ukraine to increase its export potential in the flour milling products market. The article reveals the main criteria for choosing strategic countries for the export of flour by Ukrainian producers. The key indicators of the assessment of the competitive positions of countries are the trade balance, the dynamics of the growth of the value of imports, the import price, and the presence of enterprises producing bakery products. The study found that the strategic flour-importing countries in the European Union are France, Germany, Romania, the Netherlands, Ireland, and Poland. Great Britain has a high potential for Ukrainian imports. It is estimated that the flour import market in 2021 in the EU accounted for 22% of the world import of the product. It is noted that the cost of flour imports has been gradually increasing over the past five years. Today, Ukraine has little experience in selling flour to EU countries. The value of exports to the EU is only 0.11% of world imports to the EU, and the average price of flour is $401/ton. According to the conducted analysis, it was established that the primary enterprises are located in Italy, Germany, and Poland. It is justified that Ukrainian enterprises should pay attention to the export of products to Poland, the Netherlands, and Great Britain as countries with the most attractive competitive potential.
Market competition assessment for flour in the EU countries
Keywords: експорт борошна; торговий баланс; вартість імпорту; Європейський Союз; конкуренція на ринку; flour export; trade balance; import value; European Union; market competition